Accelerated corrosion of stainless steel and Ni-based alloys in molten NaNO3-KNO3 salt vapour phases - Qingyang Liu (1508776) (2024)
The corrosion behaviour of four commonly used corrosion-resistant alloys in eutectic nitrate salt (NaNO₃/KNO₃) and its vapour phase was examined at 565 °C for 28 days. The findings revealed significantly higher corrosion rates in the vapour phase compared to the liquid phase. Samples exposed to vapour salt exhibited severe surface damage, including spallation of the outer oxide layer, whereas those in the liquid phase showed lower chromium depletion at the corroding interface. Double oxide layer was found on both stainless steels and Ni-based alloy but with different thickness and oxide layer composition. Loose and porous Fe-Na oxide layer formed on stainless steels in vapour tended to peel off and accelerated the corrosion rate by exposing the inner layer/bulk material to corrosive environment directly. A thinner oxide layer was found on Ni-based alloy. This was identified as a dense and protective inner NiO layer with Fe oxide particles distributed above the layer. These findings highlight the critical importance of considering the potential for salt vapour corrosion during material selection for practical applications, even if most salts are of low vapour pressure. Other Information Published in: Solar Energy Materials and Solar Cells License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solmat.2024.113390